Peningkatan Hasil Belajar Ipa Dengan Penggunaan Media Gambar Melalui Pembelajaran Kooperatif Tipe STAD Kelas IV SDN 024 Rambah - Yusmarni Yusmarni (JURNAL PENDIDIKAN ROKANIA, 2018)
This action research generally aims to improve science learning outcomes in grade 4 students through the use of image media with cooperative learning method type STAD in second semester of SDN 0024 Rambah. The data in this study were collected using tests, student observation sheets, teacher observation sheets, and field notes. The type of research is classroom action research. The research procedure consists of planning, execution, observation and reflection. The results revealed that preliminary test results showed that students’ absorpsion in cycle I 65.38% while cycle II was 92.30%. Based on the research conducted, it is concluded that the use of image media with cooperative learning method type STAD in grade 4 students of SD Negeri 024 Rambah can improve learning outcomes